2017
DOI: 10.1177/1729881417707148
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and experiments of a soft robotic gripper in amphibious environments

Abstract: This article presented the optimization parameter of a bidirectional soft actuator and evaluated the properties of the actuator. The systematic simulation was conducted to investigate the effect of the top wedged angle (the angle for the wedged shape of the actuator structure) of the chamber on the bending extent of the actuator when it is deflated. We also investigated the width of the actuator and the material combinations of the two layers with the relation to the deformation performance. A mathematical mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(45 citation statements)
references
References 38 publications
(43 reference statements)
0
42
0
Order By: Relevance
“…Galloway et al showed the manipulation of delicate deep reefs (Figure ) and Zhou et al reported picking up of various food items, such as a banana, a pear, a piece of tofu, and an egg, using the integration of special materials in the palms of the grippers: a memory foam sheet and a patterned elastomeric layer. Manipulation of objects in amphibious environment was demonstrated by Hao et al…”
Section: Gripping By Actuationmentioning
confidence: 99%
“…Galloway et al showed the manipulation of delicate deep reefs (Figure ) and Zhou et al reported picking up of various food items, such as a banana, a pear, a piece of tofu, and an egg, using the integration of special materials in the palms of the grippers: a memory foam sheet and a patterned elastomeric layer. Manipulation of objects in amphibious environment was demonstrated by Hao et al…”
Section: Gripping By Actuationmentioning
confidence: 99%
“…This table seeks to show the range and versatility different technologies possess. In Figure 12, for example, ECF's have very small applied forces from them for very precise movements at the cost of high power consumption due to the high pressurization requirement that inherently comes with ECF based actuators [77,123,126,127]. Knowing which situations certain soft robotic technologies are appropriate is beneficial to the ability to accurately model and create designs.…”
Section: Modelingmentioning
confidence: 99%
“…FEA model of a soft robotic actuator compared to experiment[123]. (a) Schematic of the chamber shape, (b) The maximum bending angles of the three actuators when deflated, (c) The FEA results of the three actuators at pressurization state (20 kPa).…”
mentioning
confidence: 99%
“…Materials with good stretchability can be used for building soft robots, with examples including shape memory alloys (SMAs) [2][3][4], shape memory polymers (SMPs) [5], electro-active polymers [6], acrylic [7] and silicone elastomers (i.e., polydimethylsiloxane (PDMS) [8] as well as silicone gel [4,9,10]). Soft robots that mimic the movement of animals have been explored, including a robot finger [8], soft cylindrical manipulator [11], soft gripper [12][13][14], starfish [4] and octopus tentacle [9]. Applications of soft robots for locomotion [4], bending and shape detection [11], movement detection [12], as well as temperature and strain sensing [8], have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%